1994
DOI: 10.1021/bp00029a001
|View full text |Cite
|
Sign up to set email alerts
|

5‐Aminolevulinic Acid: A Potential Herbicide/Insecticide from Microorganisms

Abstract: 5‐Aminolevulinic acid (ALA), an intermediate of the biological tetrapyrrole synthesis, can be used as a photodynamic herbicide/insecticide. Among the various microorganisms capable of its production, anoxygenic phototrophic bacteria produce ALA in considerable amounts, making it worthwhile to work toward commercial exploitation. Knowledge of the biochemical synthesis of ALA and its physiological and genetic regulation in microorganisms can enable the biotechnologist to manipulate them for enhancing ALA product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 90 publications
(61 reference statements)
1
39
1
1
Order By: Relevance
“…However, this finding was in contrast to that reported by Zhang et al (2008) who found that the MDA content had a positive relationship with ALA treatment. This was probably due to the concentration of ALA employed in the experiment of Zhang et al (2008) was much higher than in our study (0.2 vs. 50 μg mL -1 , respectively), and ALA applied at a high concentration could act as a herbicide (Sasikala et al, 1994). The data of the present study also indicated that rice seed priming with ALA at a concentration of 0.2 μg mL -1 produced no harmful effects on the seedlings although the seed had been subjected to accelerated ageing treatment.…”
Section: Discussioncontrasting
confidence: 62%
“…However, this finding was in contrast to that reported by Zhang et al (2008) who found that the MDA content had a positive relationship with ALA treatment. This was probably due to the concentration of ALA employed in the experiment of Zhang et al (2008) was much higher than in our study (0.2 vs. 50 μg mL -1 , respectively), and ALA applied at a high concentration could act as a herbicide (Sasikala et al, 1994). The data of the present study also indicated that rice seed priming with ALA at a concentration of 0.2 μg mL -1 produced no harmful effects on the seedlings although the seed had been subjected to accelerated ageing treatment.…”
Section: Discussioncontrasting
confidence: 62%
“…For example, g-valerolactone may be used as a liquid fuel, food additive and solvent; [12] 5-aminolevulinic acid is a highly active, biodegradable, and nontoxic herbicide and insecticide. [13] Additionally, pyrrolidines, such as 5-methyl-N-(methyl, aryl, alkyl, cycloalkyl)-2-pyrrolidone, are used as industrial solvents, surfactants, and complexing agents. [14] They are also employed in pharmaceutical formulations, transdermal patch formulation, grease removal formulation, agrochemical composition and stripping formulation.…”
mentioning
confidence: 99%
“…превращала пиразин (CLXXVI) в пиразиновую кислоту (CLXXVII) [Sasikala et al, 1994]. Культура Pseudomonas putida ATCC 33015 превращала 2,5-диметилпиперазин (CLXXVIII) в 5-метилпиперазин-2 карбоновую кислоту (CLXXIX) [Kiener, 1992]: Было показано, что Pseudomonas spp.…”
Section: растущая культура Rhodopseudomonas Palustrisunclassified